Horizontal Mergers, Entry and International Trade. Issue 5 (14th July 2014) - Brito, Duarte; Magueta, Daniel
<x xml:space="preserve">Abstract</x> We use a two‐country trade model to analyze an authority's decision to approve or reject a merger followed by entry, when the entrant can choose where to locate. We show that approval of a merger in the small country followed by timely, likely and sufficient entry may lead to lower consumer welfare than its rejection: when the alternative to such entry is entry into another country that also benefits consumers through trade, then the gains of attracting entry are small. In this context, we discuss differences between optimal decisions by the small country's authority, large country's authority and supranational authority.